THE TRANSFORMATION OF FOLKLORES INTO PLAY SCRIPTS FOR DRAMA LEARNING (TRANSFORMASI CERITA RAKYAT KE DALAM NASKAH LAKON BERBAHASA INGGRIS DALAM PEMBELAJARAN DRAMA) - Ambhita Dhyaningrum; Hanifa Pascarina (Leksema: Jurnal Bahasa dan Sastra, 2020)
In etnopedagogic-based drama learning by the students of English Study Program, the exploration of local wisdom values can be carried out among others by transforming folklores into play scripts in English. The transformed folklores can  then be performed on stages. In the process of transforming  a script from its hypogram, a supporting skill in the form of integration between creative writing and English as a Foreign Language Mastery (EFL) mastery is absolutely necessary. Therefore, it takes an interdisciplinary approach between those two domains of expertise to succeed the transformation process. This research employed descriptive-qualitative method with contextual grounded case study approach. It was aimed at describing the process of transformation of Banyumas folklore texts to English play scripts ranging from the intrinsic elements to the language aspects in the play. The findings showed that there were changes in the characters, settings, plots as well as the conflicts of the stories. Meanwhile, regarding the language used, there were found a number of grammatical mistakes in using possessive pronouns, verbs, word order, tenses, and diction.